Fiscal Multiplier Estimation for Kazakhstan’s Economy - R. A. Bekishev; Y. A. Pak; Z. Z. Aigazin (Экономика: стратегия и практика)
The strengthening of the role of fiscal policy in Kazakhstan in recent years has updated studies of the impact of its instruments on the economy. In this regard, the assessment of the fiscal multiplier is an important research task that has practical significance for increasing the effect of fiscal policy. The purpose of this article is to estimate the fiscal multiplier in Kazakhstan. The quarterly data for the period from 2000 to 2022 from the official statistical sources of information were used. For the specified time period, the authors made two distinct estimates of the fiscal multiplier of Kazakhstan’s public expenditures: with and without considering economic cycles. The comparison of the simulation results allowed the authors to note the shortcomings of the fiscal multiplier estimation without considering economic cycles. In the cycle-ignoring model, the lag of government spending shock was overestimated. Moreover, the fiscal multiplier without cycles turned out to be significant at the 10% significance level and amounted to only 0.2. The fiscal multiplier in the model with cycles during the recession period turned out to be significant at the 1% significance level and amounted to 0.44, and during the expansion period,, it turned out to be insignificant for any lag. Based on these results, the authors conclude that the theoretical importance of fiscal measures in a recession is confirmed for Kazakhstan. However, during a period of economic growth above the potential level, an additional positive shock of government spending will not lead to positive effects on the economic growth.